SUMBER DAYA MANUSIA DALAM MEWUJUDKAN GOOD GOVERNANCE - Dignasia Junita E.42008088 (FISIP Universitas Tanjungpura Pontianak, 2012)
The research is intended to product recommendation in an effort to improve of the human resources forGood Governance in West Singkawang goverment office. The title of this research was appointed problems onthe factors that effect the relation to the implementation of the effectiveness and efficiency is not maximized.This research used a kualitatif research model which was carry through several stage. The stage includefinding problems, formulate, and make recommendations on the findings are. Research sites in Singkawang Citywith the research subject are Singkawang Head of West, Secretary, Head of subdivision office personal, andsome staff.The conclution of the research is not maximal implementation of one principle Good Governance, theprinciple is effectiveness and efficiency which principle related to improving the quality of human resourcesespecially the factor influencing the level of education and staff motivatic frequency. For that, therecommendation is addition of the frequency and quality improvement such as education and training andtechnical as well as Head’s approach to increasing staff motivated employees. Keywords: human resources, Good Governance, effectiveness and efficiency